Optimalisasi Regulasi Diri Santri Wustho dalam Menghadapi Era Digital - Refi Mariska; Siti Mumun Muniroh (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The digital era brings challenges as well as opportunities for Wustho students in managing self-regulation, especially in the use of technology and digital media. This study aims to analyze the optimization strategy of self-regulation of Wustho students in facing the digital era, focusing on aspects of time management, self-control, and technology adaptation. A qualitative approach is used in this study, involving observation, in-depth interviews, and document analysis. The results of the study show that student self-regulation can be improved through the integration of education-based technology, digital discipline habituation, and independence training programs. This strategy not only helps students in managing their daily activities but also supports the achievement of learning goals more effectively. The implications of this study provide practical guidance for Islamic educational institutions to prepare students to become independent and adaptive individuals in the era of digital transformation. The findings of this study are that strengthening spiritual-based intrinsic motivation can be an effective strategy to build self-regulation among students. This approach offers uniqueness, namely connecting religious values with self-management skills in the digital era, thus providing a strong moral foundation for students in using technology wisely. The implications of this study highlight the need for pesantren policies that are more adaptive to digital developments, while still maintaining Islamic identity as a core value in pesantren education.